Improvement of User Experience Evaluation For SMEs Digital Application Using TRI, TAM, SUS Integration - Ismanto, Ivan; Gamayanto, Indra; Sanyoto, Gabriello Klavin (Politeknik Negeri Batam, 2026)
Micro, Small, and Medium Enterprises (MSMEs) in the service sector, particularly vehicle wash services, continue to face challenges related to queue management, service transparency, and operational efficiency, which negatively affect user experience. This study aims to develop and evaluate a mobile-based service booking and management application prototype by integrating the Design Science Research (DSR) approach with the Technology Readiness Index (TRI), Technology Acceptance Model (TAM), and System Usability Scale (SUS) as an evaluation framework. The artifact was developed through DSR stages, including problem identification, design, demonstration, and evaluation. Qualitative data were collected through interviews with MSME owners, employees, and customers and analyzed using Thematic Analysis. Quantitative evaluation involved 106 respondents to measure technology readiness, user acceptance, and usability quality, accompanied by a descriptive analysis of relationships among the constructs. The results indicate a high level of technology readiness (TRI = 3.53) and very strong user acceptance (TAM = 4.27). However, the usability score falls within the marginal acceptable category (SUS = 62.95), indicating a gap between conceptual acceptance and actual interaction quality. These findings demonstrate that integrating TRI–TAM–SUS within the DSR framework effectively identifies critical contradictions that can serve as a basis for refining UI/UX design and implementation strategies for digital applications in service-based MSMEs.